PPI-based screening of hub genes related to sepsis migration/pyroptosis and immune infiltration analysis - Xu Ma; Jianhao Wang; Kun Han; Jinshuai Lu (PLoS ONE, 2025)
Background Sepsis incidence is rising, but its pathogenesis remains unclear. This study aimed to identify therapeutic targets. Methods Three GEO datasets (GSE154918, GSE32707, GSE54514) were analyzed after batch correction. Differentially expressed genes (DEGs) were identified, and those related to pyroptosis/migration were cross-analyzed. Functional enrichment (GO/KEGG) and interaction networks (PPI, mRNA-miRNA, mRNA-TF, mRNA-drug) were constructed. External validation used GSE57065, excluding non-significant genes. ROC analysis and immune infiltration were performed. Results 3566 DEGs (1715 up, 1851 down) were identified, with 23 linked to pyroptosis/migration. Enrichment analysis highlighted roles in cell adhesion, cytokine regulation, and pathways like IL-17, TNF, and Toll-like receptor signaling. mRNA-miRNA interactions for 12 key genes were predicted. After validation, eight key genes remained: TLR2, SIRT1, PTGS2, MAPK14, IL18, ICAM1, CD274 , and CASP3 . Immune infiltration revealed varied effects on MAPK14. Conclusion Key gene alterations may serve as sepsis biomarkers, and miRNA dysregulation could play a critical role in sepsis pathophysiology.